Influence of domains of self-autonomy and self-efficacy on Academic performance of secondary school students in Kenya - Ndiewo, Paul Oduor (JOOUST School of Education, 2016)
Academic performance of secondary school students is a great concern in many nations because of its direct impact on development of the nations. Good academic performance guarantees admission into higher institutions of learning and quality of manpower. Students’ academic performance is a matter of concern and many nations and scholars are looking for ways of alleviating the problem of poor academic performance.Academic performance affects nations in many ways because potential future labour force is threatened while possibility of crime rate, social evils and dependency rate increases. Academic performance among students may be a function of many factors such as their abilities, socio-economic background and pedagogical beliefs. The purpose of the study was to establish influence of domains of self-autonomy and self-efficacy on academic performance of secondary school students in Bondo Sub-County. This study was guided by the following objectives: To investigate the influence of learners’ involvement on academic performance, to findout the influence of learners’ reflection on academic performance, to establish the influence of academic self-efficacy on academic performance and to determine the influence of learners’ social self-efficacy on academic performance. The study was guided byLocke and Lotham’s achievement theory.Mixed study approach was adopted in the study.The target population was 2500students and 357 teachers. Stratified sampling was used to select 12 secondary schools while simple random sampling was used in this study to select 407 students. The researcher used purposive sampling to select 12 form four class teachers. The researcher administered questionnaires and interviews to establish levels of learner-autonomy and self-efficacy of the selected students while document analysis was used to determine academic performance of the participants. Content validity of the research instrument was enhanced through a pilot study using students not under the study. Reliability was determined by internal consistency method in which coefficient alpha of = 0.777 was obtained. Qualitative data was analysed using thematic analysis while descriptive and inferential statistics such as Pearson product moment correlation were used to analyse quantitative data with the aid of SPSS version 22. A statistical significant relationship r = .17, p ≤, 05 was established between learner involvement and academic performance. There was a significant positive correlation r = .173, p ≤ .05 between learner reflection and academic performance. A significant positive correlation r = .190, p ≤.05 was found between social efficacy and academic performance. A positive correlation r = .139, p ≤ .05 was found between academic self-efficacy and academic performance of secondary school students. The study recommended that teachers and school counselors should encourage students to be engaged in learning activities. The study also recommended that schools should enhance peer tutoring to help students adjust to learning environment.